The oceans, their physics, chemistry, and general biology - Sverdrup, H. U. (Prentice-Hall, 1961)
Contents: The Earth and the ocean basins; Physical properties of sea water; General distribution of temperature, Salinity, and density; Chemistry of sea water; Organisms and the composition of sea water...